Preschool Children’s Memory for Word Forms Remains Stable Over Several Days, but Gradually Decreases after 6 Months - Gordon, Katherine R.; McGregor, Karla K.; Waldier, Brigitte; Curran, Maura K.; Gomez, Rebecca L.; Samuelson, Larissa K. (Frontiers in Psychology, 2016)
Research on word learning has focused on children’s ability to identify a target object when given the word form after a minimal number of exposures to novel word-object pairings. However, relatively little research has focused on children’s ability to retrieve the word form when given the target object. The exceptions involve asking children to recall and produce forms, and children typically perform near floor on these measures. In the current study, 3- to 5-year-old children were administered a novel test of word form that allowed for recognition memory and manual responses. Specifically, when asked to label a previously trained object, children were given three forms to choose from: the target, a minimally different form, and a maximally different form. Children demonstrated memory for word forms at three post-training delays: 10 minutes (short-term), 2 to 3 days (long-term), and 6 months to 1 year (very long-term). However, children performed worse at the very long-term delay than the other time points, and the length of the very long-term delay was negatively related to performance. When in error, children were no more likely to select the minimally different form than the maximally different form at all time points. Overall, these results suggest that children remember word forms that are linked to objects over extended post-training intervals, but that their memory for the forms gradually decreases over time without further exposures. Furthermore, memory traces for word forms do not become less phonologically specific over time; rather children either identify the correct form, or they perform at chance.